2016
DOI: 10.1021/acs.nanolett.6b00034
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Random Lasing with Three-Dimensional Plasmonic Nanorod Metamaterials

Abstract: Plasmonics has brought revolutionary advances to laser science by enabling deeply subwavelength nanolasers through surface plasmon amplification. However, the impact of plasmonics on other promising laser systems has so far remained elusive. Here, we present a class of random lasers enabled by three-dimensional plasmonic nanorod metamaterials. While dense metallic nanostructures are usually detrimental to laser performance due to absorption losses, here the lasing threshold keeps decreasing as the volume fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 44 publications
6
59
2
Order By: Relevance
“…In addition, the features of lasing spectra in Ref. 59 are consistent with the behavior exhibited in random lasers with coherent feedback 60 , and thus are distinct from the observations in this work.…”
Section: Toc Graphicsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the features of lasing spectra in Ref. 59 are consistent with the behavior exhibited in random lasers with coherent feedback 60 , and thus are distinct from the observations in this work.…”
Section: Toc Graphicsupporting
confidence: 83%
“…It is noteworthy to mention that the lasing herein is distinct from that reported in a previous work based on tilted silver nanorods in terms of sample configuration and lasing mode dispersion 59 . In…”
Section: Toc Graphiccontrasting
confidence: 72%
See 1 more Smart Citation
“…Wang et al . suggested that the optimal amount of metallic nanoparticles in an amplifying random medium was related to the dominance of scattering over absorption for metallic nanoparticles . The authors proposed to use cross‐section ratio, σ sca /σ abs , as a semi‐empirical parameter to characterize the dominance degree of scattering over absorption.…”
Section: Plasmonic Random Lasermentioning
confidence: 99%
“…54 Densely packed Ag nanorods in arrays, realized by a glancing angle deposition method and tilted at about 30 • with respect to a substrate, induce random lasing in polymer films doped with rhodamine. 55 Forming a plasmonic metamaterial, the nanorods assist the formation of confined laser modes and decrease the lasing threshold up to considerably high packing fraction (7% of metal). Metal nanoparticles can also be directly electrospun together with polymers, thus leading to achieve plasmon-enhanced random lasers.…”
Section: -3mentioning
confidence: 99%